Locally delivered modified citrus pectin - a galectin-3 inhibitor shows expected anti-inflammatory and unexpected regeneration-promoting effects on repair of articular cartilage defect. (December 2022) - Zhang, Yiyun; Su, Danning; Wang, Yimeng; Wang, Ziqiang; Ren, Ying; Liu, Rui; Du, Bo; Duan, Ruiping; Shi, Yanping; Liu, Lingrong; Li, Xuemin; Zhang, Qiqing
Abstract: Treating the concomitant inflammation in the process of injury and repair, and simultaneously promoting cartilage regeneration is very important for the repair of articular cartilage (AC) defects. Nevertheless, this remains a massive challenge. To address this issue, a collagen membrane-based modified citrus pectin (MCP) delivery system (MCP-C) was developed in this study by targeting galectin-3 (Gal-3), an upstream proinflammatory factor. As expected, MCP shows anti-inflammatory effects; it downregulates the expressions of IL-1β, MMP13, Gal-3, and COL1A2, inhibits the degenerative effects of Gal-3 on chondrocytes in vitro, and protects chondrocytes from degeneration and death in vivo . Unexpectedly, MCP promotes the proliferation of chondrocytes, upregulates the expression of COL2A1 and SOX9 in the chondrocytes in vitro, and enhances the repair of AC defect in rabbit knee, especially MCP500 -C with a complete release of the loading amount of approximately 500 μg/cm 2 in a day. Mechanistically, MCP upregulates the expressions of multiple endogenous growth factors for chondrogenesis via the transcriptome sequencing of MCP-treated chondrocytes, and downregulates the expressions of various inflammatory factors. These findings demonstrate that locally delivered MCP can simultaneously modulate both regenerative and inflammatory responses, and can enhance the repair of AC defects.